PENGARUH ROB DAN ABRASI TERHADAP PENDAPATAN PETANI TAMBAK BANDENG (Studi Kasus Desa Sidogemah Kecamatan Sayung Kabupaten Demak Jawa Tengah) - Ahmad Romadhon; Dewi Hastuti; Rossi Prabowo (Universitas Wahid Hasyim, 2014)
This study aims to determine the socio-economic characteristics, land area and income of farmers affected milkfish rob and abrasion in the village Sidogemah Sub-District Sayung Regency Demak. The area was chosen as a test site set deliberately, based on consideration of the area that the vast amount of the most extensive fishpond to day. Sampling was done by the method of census respondent, where each element of the population that is being recorded and given a chance of being selected in to the sample. Socio-economic characteristics of fish farmers based on descriptive analysis that fish farmers their views of live area still productive but education is getting old and is still 12 years old, old enough experience and the number of family members on average more than 5 people. A decrease in land area of 2,40 ha fishpond before exposure to rob and abrasion exposed to 1,77 ha after rob and abrasion. Total cost increases on farm land that has its own land of Rp 543.011,16 to Rp 840.231,82 and palso which has leased land from Rp 765.745,76 to Rp 1.062.966,42, resulting in decreased before exposure to rb acceptance or Rp 2.931.923,08 and after exposed to rob Rp 2.801.636,90. A reduction in income milkfish farmers who have their own land of Rp 2.388.911,92 prior to exposure to rob and abrasion to Rp 1.961.405,08, also on fish farmers who have leased land from Rp 2.166.186,32 prior to exposure to rob and abrasion Rp 1.868.956,66 after exposure to rob and abrasion of the land area of 1,77 ha fishpond/person. So the hypothesis first and second can be accepted. Keywords : Abrasion, income, fishpond, milkfish,rob